STUDENTS’ PREFERENCES FOR AI TOOLS IN ENHANCING THEIR ENGLISH ORAL PRESENTATION SKILLS - Lai, See May; Rosly, Rohazlyn; Mohd Firdaus Kozako, Intan Nurul ‘Ain; Nik Mohd Shafriman, Nik Zaireen Batrisyia; Nik Ruslan, Nik Nur Qistina; Zunaidi , Siti Nurdamia (Journal of Islamic, Social, Economics and Development, 2024)
This study investigates students' preferences for Artificial Intelligence (AI) tools in enhancing their English oral presentation skills. The research aimed to identify the specific AI-powered features and functionalities that students find most helpful in improving various aspects of their English presentations, such as language proficiency, delivery, and overall performance. The study employed a survey methodology to collect data from a sample of 135 diploma students enrolled in the ELC270 English for Workplace Communication course at Universiti Teknologi MARA (UiTM) Cawangan Kelantan. The results indicate that students highly value the use of AI tools in areas such as vocabulary building, grammar correction, pronunciation feedback, and presentation structure analysis. Participants also expressed a strong preference for AI-powered features that provide real-time feedback, personalized recommendations, and interactive practice opportunities. The findings highlight the important role that AI-based technologies can play in supporting the development of students' English oral presentation skills. By leveraging the capabilities of AI, educational institutions can better address the challenges faced by students in mastering this critical academic and professional competency. The insights from this study can inform the design and implementation of AI-integrated language learning programs to enhance the learning experiences and outcomes of students.